2002
DOI: 10.1289/ehp.02110s5871
|View full text |Cite
|
Sign up to set email alerts
|

A role for associated transition metals in the immunotoxicity of inhaled ambient particulate matter.

Abstract: Epidemiologic studies demonstrate that infection, specifically pneumonia, contributes substantially to the increased morbidity and mortality among elderly individuals following exposure to ambient particulate matter (PM). This laboratory has previously demonstrated that a single inhalation exposure of Streptococcus pneumoniae-infected rats to concentrated ambient PM 2.5 (particulate matter with aerodynamic diameter ≤ 2.5 µm) from New York City (NYC) air exacerbates the infection process and alters pulmonary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 36 publications
0
38
1
2
Order By: Relevance
“…These reports have been supported by studies in rodent models that provide evidence that PM can modulate pulmonary immune responses (47). The observed interactions between Ni and MALP-2 on the elaboration of chemokine release from HLF suggest that pulmonary immune responses in humans may also be altered as a consequence of PM exposure.…”
Section: Discussionmentioning
confidence: 77%
“…These reports have been supported by studies in rodent models that provide evidence that PM can modulate pulmonary immune responses (47). The observed interactions between Ni and MALP-2 on the elaboration of chemokine release from HLF suggest that pulmonary immune responses in humans may also be altered as a consequence of PM exposure.…”
Section: Discussionmentioning
confidence: 77%
“…Recent animal studies suggest that PM or its constituents play a role in affecting host defenses and increase susceptibility to pulmonary infections. [411][412][413] Hypoxemia Another mechanistic pathway involves PM-induced lung damage (potentially including oxidative lung damage and inflammation), declines in lung function, respiratory distress, and hypoxemia. In the case report discussed above, 332 exposure to high levels of aerosolized oil fly ash particles eventually led to the experiencing of hypoxic respiratory failure.…”
Section: Modulated Host Defenses and Immunitymentioning
confidence: 99%
“…33 Particulate matter is likely immunosuppressive and may undermine normal pulmonary antimicrobial defense mechanisms. 34 Additional studies are needed to explore the potential mechanisms.…”
Section: Coarse Particles and Respiratory Infections In Childrenmentioning
confidence: 99%
“…33 Particulate matter is likely immunosuppressive and may undermine normal pulmonary antimicrobial defense mechanisms. 34 Additional studies are needed to explore the potential mechanisms.In our study, some gaseous pollutants showed significant effects on hospitalization for respiratory infections, but the influences were no longer significant when particulate matter was taken into consideration. The only exception is the effect of NO 2 in girls, which remained significant even after controlling for particulate matter.…”
mentioning
confidence: 99%